Successful shoot tip grafting of cacao (Theobroma cacao L.) due to the application of plant growth regulators on various concentrations - Sari, Wulan Kumala; Utami, Nia Putri (Kultivasi, 2024)
Cacao plays an important role in the Indonesia economy. Therefore, its production and area expansion have to increase to achieve maximum cacao productivity by the quality and superior cacao clones. Shoot tip grafting is one of the propagation methods to obtain superior cacao plants by applying Plant Growth Regulators (PGRs). Research on the effect of several PGRs with various concentrations on cacao (Theobroma cacao L.) shoot tip grafting was conducted at the Integrated Innovation Farmer Group, Belubus, Sungai Talang Village, Guguak District, Lima Puluh Kota Regency, West Sumatra from February until June 2022. This study aimed to determine the interaction between PGR type and concentration on the grafting success and growth of cacao shoot tip grafted seedling. The research was designed by a Factorial Completely Randomized Design with three replications. The first factor was the type of PGR, i.e., synthetic PGR (BAP), young corn seed extract, shallot extract, and young coconut water. The second factor was the concentration of PGR, i.e., 0%, 25%, 50%, 75% and 100%. The results showed an interaction between PGRs with some concentrations on the number of shoots, shoot length, and leaf length on the grafted cacao seedling. The natural PGR from young coconut water at a concentration of 75% gave the best effect on the number of shoots (3.33 shoots) and shoot length (24.50 cm) of cacao seedling.